Clinical considerations and surgical outcomes of breast implant-associated cancer: An emerging disease of interest: Consideraciones clínicas y desenlaces quirúrgicos del cáncer asociado a implante mamario: Una enfermedad emergente de interés - Manjarres Guevara, Abel Enrique (2023)
Breast cancer continues to be one of the main priorities in global health and public health, and remains the most frequent and deadly malignant neoplasm in women worldwide. Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare type of non-Hodgkin's lymphoma, whose pathogenesis and pathophysiology are not well known, but which is seen with increasing frequency due to the increase in cosmetic procedures. To date, there are limitations in terms of knowledge about the clinical behavior of the disease, which can manifest itself in many forms, with a variable evolution time and uncertain surgical outcomes in the medium- and long-term. Based on the above, the aim of this review is to summarize evidence on the clinical considerations and surgical outcomes of breast implant-associated cancer to facilitate the identification and management of this condition. A bibliographic search was performed in the search engines and databases PubMed, ScienceDirect, Embase, EBSCO and MEDLINE. Within the clinical and surgical considerations, the type of implant used (textured), the time of the implant history, the severity of the manifestations, and the staging, must be taken into account in order to determine the opportunity for surgical intervention and neoadjuvant therapy, and to try to guarantee survival and avoid recurrence. Patients who undergo complete capsulectomy with radiotherapy have better outcomes.